2022
DOI: 10.1007/s00277-022-04964-y
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis and COVID-19: experience from an amyloid program in Canada

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV2) and associated COVID-19 infection continue to impact patients globally. Patients with underlying health conditions are at heightened risk of adverse outcomes from COVID-19; however, research involving patients with rare health conditions remains scarce. The amyloidoses are a rare grouping of protein deposition diseases. Light-chain and transthyretin amyloidosis are the most common disease forms, often present with systemic involvement of vital organs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Whilst the specific breakdown of the amyloidosis group was not reported, these patients who were admitted to hospital had a significantly raised mortality rate of 28%. Similar findings were presented by Lewis et al [ 16 ], who evaluated a cohort of 152 ATTR patients and 103 AL amyloidosis patients during the period between January 2020 and April 2022. They found that patients with amyloidosis were at high risk of severe infection and mortality from COVID-19, in particular those of older age and receiving active immunotherapy.…”
Section: Clinical Outcomes Of Covid-19 Infection In Patients With Amy...supporting
confidence: 86%
See 3 more Smart Citations
“…Whilst the specific breakdown of the amyloidosis group was not reported, these patients who were admitted to hospital had a significantly raised mortality rate of 28%. Similar findings were presented by Lewis et al [ 16 ], who evaluated a cohort of 152 ATTR patients and 103 AL amyloidosis patients during the period between January 2020 and April 2022. They found that patients with amyloidosis were at high risk of severe infection and mortality from COVID-19, in particular those of older age and receiving active immunotherapy.…”
Section: Clinical Outcomes Of Covid-19 Infection In Patients With Amy...supporting
confidence: 86%
“…The combination of quarantine measures and the disruption of non-emergency healthcare services resulted in reduced access to healthcare for patients with chronic diseases, such as amyloidosis [ 20 , 21 ]. Furthermore, those with new or relapsing disease were likely to experience delays in diagnostics and treatment facilities were often limited and or restricted [ 16 , 18 ]. Telemedicine has been reported as one of the adaptation measures which enhanced the continuation of care for amyloidosis patients during the early stages of the pandemic [ 16 , 18 , 22 , 23 ].…”
Section: Impact Of Covid-19 Pandemic On the Management Of Amyloidosismentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular association of SARS-CoV-2 infection is likely detrimental and a possible worsening of ongoing ATTR amyloidosis [ 142 ]. Systemic amyloidosis patients (AL and ATTR) showed excess mortality when suffering from COVID-19 compared to otherwise healthy individuals [ 143 ].…”
Section: Covid-19 Sequelae With Similarities and Possible Connections...mentioning
confidence: 99%